Basic theory and design method of variable shaft angle line gear mechanism - Chen, Yang-zhi (Strojniški vestnik, 2021)
In this paper, a novel line gear mechanism is proposed; it is called the variable shaft angle line gear mechanism (VSALGM). VSALGM has two rotational degrees of freedom, one is the rotation of the two gears with a constant transmission ratio, and the other is the relative swing of the two gears shafts. First, a novel contact model of VSALGM composed of one driven contact curve and one driving line teeth working surface (DLTWS) was proposed. With the concept, the basic design equations for VSALGM were derived on the basis of the space curve meshing theory of line gear. Moreover, the design criterion of pressure angle for VSALGM was analysed and proposed on the basis of the contact model. A basic design method for VSALGM was thus developed. A design example was given, and prototypes were manufactured using three-dimensional (3D) printing. Kinematic experiments and gear contact spot testing were carried out on a self-made kinematic test rig by the prototypes. The results show that the VSALGM designed in this paper can achieve a continuous, smooth and stable meshing transmission while the shaft angle is continuously changed within its setting range.
Keywords: degree of freedom; kinematični eksperiment; line gear; linijski zobniki; pressure angle; prostostna stopnja; space curve meshing theory; teorija prostorske ubirnice; ubirni kot; variabilen kot gredi; variable shaft angle; zobniški prenos